Sustainability and accountability of social enterprise / Nur Hayati Ab Samad … [et al.] - Ab Samad, Nur Hayati; Arshad, Roshayani; Asat, Siti Haliza; Kasim, Nawal (Universiti Teknologi MARA Cawangan Selangor, 2017)
Accountability is a pervasive issue for social entrepreneurial non-profit organisations (NPOs), which are also known as social enterprises as they seek to balance their social mission with financial responsibility. With the increased need for accountability, social enterprises need to identify the relevant factors of sustainability since increased in the scope and size of the social enterprise will indirectly trigger sustainability issue. Thus, this study aims to examine the extent of social enterprise’s sustainability in relation to the relevant factors that affect organisational sustainability. The four main factors are leadership capacity, adaptive capacity, management and technical capacity and financial viability. Content analysis was used to measure the extent of sustainability from the information disclosed in annual reports by 210 organisations registered under the Registry of Societies (ROS) in Malaysia. Findings from the study indicate that most of the social enterprises are aware that effective leadership is vital for organisational sustainability. However, management and technical aspects tend to be neglected possibly due to lack of adequate resources and facilities to adapt to current changes. Overall, this study highlights that in order to discharge accountability, the social enterprise need to appropriately address relevant factors that influence organisational sustainability especially on management and technical aspect in achieving the balance between social mission and financial responsibility.